Design and Fabrication of Ni3P2O8-Co3P2O8·8H2O as Advanced Positive Electrodes for Asymmetric Supercapacitors. (20th May 2016) - Liu, Mao-Cheng; Li, Jia-Jia; Hu, Yu-Xia; Yang, Qing-Qing; Kang, Long
Abstract: Nano-sized Ni3 P2 O8 -Co3 P2 O8 ·8H2 O is synthesized via a facile chemical precipitation method as the active material of supercapacitors. The experiment result expresses the Ni3 P2 O8 -Co3 P2 O8 ·8H2 O of the Ni/Co molar ratio of 8:2 exhibits enhanced capacitive behaviors relatively than others, it delivers a highest mass specific capacitance of 1974 F g −1 at 0.5 A g −1, which is higher than both Ni3 P2 O8 and Co3 P2 O8 ·8H2 O. The sforzato in specific capacitance is on account of the pore structure, uniform particle morphology, and hyperbaric of Ni. An asymmetric supercapacitor is assembled using the Ni3 P2 O8 -Co3 P2 O8 ·8H2 O and activated carbon (AC) as positive and negative electrode, respectively. It not only sends a large specific capacitance (94 F g −1 ) but also good cycling stability (up to 5000 cycles). The impressive results presented here may be potential applications for high energy density storage systems.